2022
DOI: 10.3349/ymj.2022.63.8.767
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Underuse of Sedatives and Neuromuscular Blocking Agents for Pediatric Emergency Endotracheal Intubation in Korea

Abstract: Purpose Rapid sequence intubation (RSI) using sedatives and neuromuscular blocking agents (NMBAs) is recommended for pediatric emergency endotracheal intubation (ETI), but is not frequently performed in Korea. This study aimed to verify factors associated with the underuse of RSI medications. Materials and Methods This multicenter retrospective study reviewed patients aged under 18 years who underwent an ETI within 24 hours of arrival at the emergency department between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…One of the attempts to prevent hypoxia in RSI is apneic oxygenation, consisting of providing oxygen to the patient in apnea during laryngoscopy and insertion of the orotracheal tube. In our review, the study found by Overmann et al 12 did not indicate benefits from this approach. However, a specific integrative review on the topic, published in 2019, indicated that there may be benefit to this procedure, although there is no strong evidence in the literature.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…One of the attempts to prevent hypoxia in RSI is apneic oxygenation, consisting of providing oxygen to the patient in apnea during laryngoscopy and insertion of the orotracheal tube. In our review, the study found by Overmann et al 12 did not indicate benefits from this approach. However, a specific integrative review on the topic, published in 2019, indicated that there may be benefit to this procedure, although there is no strong evidence in the literature.…”
Section: Discussionmentioning
confidence: 54%
“…Although the use of medications during and after RSI is well established in the literature, this review identified that many professionals who work in pediatric emergencies still do not correctly indicate medications. Lee et al 12 reported that, in younger patients or those with comorbidities, there is a greater probability of insufficient use of medications during the procedure. This is possibly due to an excessive fear of side effects, which is not justified in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation